Genetic polymorphisms, mRNA expression levels of telomere-binding proteins, and associates with telomere damage in PAHs–Exposure workers. (September 2019) - Duan, Xiaoran; Yang, Yongli; Zhang, Daping; Wang, Sihua; Feng, Xiaolei; Wang, Tuanwei; Wang, Pengpeng; Ding, Mingcui; Zhang, Hui; Liu, Bin; Wei, Wan; Yao, Wu; et al.
Abstract: Coke oven emissions (COEs), confirmed human carcinogens, are mainly composed of polycyclic aromatic hydrocarbons (PAHs). Telomere shortening in blood leukocytes has been associated with COEs, and polymorphisms in metabolic enzymes. However, the relationship between polymorphisms in telomere related genes and telomere shortening in COEs exposed workers has never been evaluated. Therefore, we measured telomere length and mRNA expression levels of telomere-binding proteins (TBPs) by qPCR method in leucocyte from 544 COEs exposed workers and 238 office staffs (referents). Flight mass spectrometry was used to perform the genotyping of selected functional and susceptible SNPs. The results showed that the telomere length in the exposure group 0.75(0.51, 1.08) was significantly shorter than that in the control group 1.05(0.76, 1.44) ( P < 0.001). The mRNA expression levels of TPP1, TERF1 and TERF2 genes in the exposure group were significantly lower than those in the control group ( P < 0.05), the mRNA expression level of POT1 in the exposure group was significantly higher than that in the control group ( P < 0.05). We used the wild homozygous genotype as a reference, subjects carrying TERT rs2736109 AA, TERT rs3215401 CC and TERT rs2736100 GT + GG genotypes had significantly longer telomere length in the exposure group ( P < 0.05). In conclusion, the workers exposed to COEs had shorter telomere length, which was regulated by the TPP1, TERF1, TERF2 and POT1 genes expression levels, and the gene polymorphisms of TERT gene were associated with the telomere length among PAHs-exposure workers. Graphical abstract: Image 1 Highlights: Workers exposed to COEs had shorter RTL, regulated by TPP1, TERF1, TERF2 and POT1 genes. TERT gene polymorphisms were associated with the RTL.